2019
DOI: 10.30870/jels.v4i1.5219
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Peer Drilling on 10th Grade Student’s Vocabulary Mastery

Abstract: This research is expected to know whether there is significant different score of vocabulary test before and after treatment has been given. This research is a quasiexperimental design where the population is Tenth Grade of SMA Muhammadiyah 2 Tangerang. The researcher took sample from X.4 class as control class and X.5 class as experiment class. The sample is 40 students for each class. In collecting the data, the researcher used interview, pretest and posttest of vocabulary and applied peer drilling as a tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…This research needs to be done based on reference data from the results of a Mulyanah study of the University of Muhammadiyah Tangerang in the PDP scheme Ristekdikti in Tangerang Regency 2019. From the research data found the problem was 97% in Tangerang Regency There is an English teacher who is not linear with the field of science so that there is difference incompetency in English mastery of elementary school students in the district, of course, this has resulted in a difference in English mastery over elementary school students in the district with the existing in the city of Tangerang (Ishak & Mulyanah, 2019). This difference can be seen from the increase in the average value of elementary school students in the district reached 49.00 while elementary school students in the city reached 66.67.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This research needs to be done based on reference data from the results of a Mulyanah study of the University of Muhammadiyah Tangerang in the PDP scheme Ristekdikti in Tangerang Regency 2019. From the research data found the problem was 97% in Tangerang Regency There is an English teacher who is not linear with the field of science so that there is difference incompetency in English mastery of elementary school students in the district, of course, this has resulted in a difference in English mastery over elementary school students in the district with the existing in the city of Tangerang (Ishak & Mulyanah, 2019). This difference can be seen from the increase in the average value of elementary school students in the district reached 49.00 while elementary school students in the city reached 66.67.…”
Section: Introductionmentioning
confidence: 98%
“…One of the media is the English instructions book. English instruction one of the techniques on the Total Physical Response (TPR) method (Ishak & Mulyanah, 2019). The goal is to maintain an initial motivation and maintain a sense of curiosity and interest the teachers' thereby developing a desire to learn the language, especially in English easily and quickly because according to (Setyanigtyas, 2018).…”
Section: Introductionmentioning
confidence: 99%